Evaluating fuel-injection motorcycle service training effectiveness using the CIPPO model - Aulia Rahman; Arwizet Karudin; Hasan Maksum; Eko Indrawan; Fadhillah Riski Aisyah Nasution (Journal of Educational and Learning Studies, 2026)
Objective: This study evaluated the Fuel-Injection Motorcycle Service Training Program at UPTD BLK Pasaman Barat using the CIPPO model. Methods: A qualitative evaluation design was employed through observations, semi-structured interviews, and document analysis involving program managers, instructors, participants, and industry stakeholders. Data were analyzed through reduction, display, and conclusion verification. Results: The program was relevant to community needs and supported by a competency-based curriculum and qualified instructors, although training facilities remained limited. All 16 participants (100%) completed the training, 11 (68.75%) obtained BNSP competency certification, and 6 graduates (37.5%) entered employment or entrepreneurship. Conclusion: The program was generally effective, but improvements are required in training facilities, certification access, industry partnerships, and graduate employment support